Indonesia constitutional court: the guardians of democracy in the pandemic era - Mokhtar, Khairil Azmin (2022)
General elections, which are carried out honestly, fairly, consistently and continuously, are efforts to maintain a democratic climate in every country. As a country that upholds democracy, Indonesia always strives to carry out general elections in an honest, fair, consistent and continuous manner every five years, as mandated by the constitution. In spite of the Coronavirus Disease 2019 (COVID-19) pandemic, Indonesia had conducted regional head elections, namely the election of governors in 9 provinces and of regents/mayors in 261 districts/cities. As the state institution guards the constitution and democracy, the Constitutional Court is obliged to resolve and manage general election disputes even during the pandemic. This paper examines the strategy and management of the Constitutional Court in handling general election dispute cases to regions during the pandemic period while maintaining the independence and impartiality of the Constitutional Court institutions. This study uses primary and secondary data, including the Indonesian Constitution, the regional election law, and other regulations related to handling regional head elections during a pandemic. This study also compares government policies related to handling regional head elections during a pandemic in Indonesia and other countries, especially regarding the rights of the people to still be able to come to Court during a pandemic. Existing data and legal materials related to handling general election disputes during a pandemic are compared and analysed in full and in detail. It is concluded that the management of case admissions and trial management using ICT technology has proven to be effective in minimising the gathering of people so that the Constitutional Court does not become a cluster of coronavirus transmission.